Transcranial Approach in Craniopharyngioma Surgery: Results from Tertiary Care Center in Nepal - Jha, Rajiv; Shrestha, Rajendra; Bhattarai, Sushil M; Gautam, Sindhu; Aryal, Sameer; Rajbhandari, Binod; Jha, Binit; Jalan, Pankaj; Prajapati, Neebha; Paudel, Kumar; Khadka, Namrata (Nepal Journal of Neuroscience, 2024)
Objective: Management of  craniopharyngiomas poses a significant challenge in neurosurgery, because of their involvement with the hypothalamus and visual systems. Complete resection attempts a higher mortality while  incomplete surgery has high recurrence rates.Methods: This is a  prospective study from the period of January 2016 to April 2024 at the National Neurosurgical Referral Center (NNRC), National Academy of Medical Sciences (NAMS) Bir Hospital. Inclusion criteria consists of all the histopathological proven cases of craniopharyngioma who underwent transcranial surgery during the study period.The analysis encompassed clinical, ophthalmological, imaging, endocrinological, neuropsychological, and surgical complication data from medical records.Results: A total of 52 craniopharyngioma cases were operated during the study period. It had a classical bimodal age distribution, with an increased incidence rate in 5 to 14 years and 50 to 74 years of age. Predominantly affecting young females, the common manifestations were visual problems ,hydrocephalus, features of raised intracranial pressure(ICP) and endocrinopathy. Most of the tumors were larger than 4 cm size with Samii and Tatagiba Grade IV.The orbitozygomatic approach was used in all cases. Gross-total resection was achieved in 80% of patients, near-total in 12%, and partial in 8%. Postoperative complications included Diabetes Insipidus and hormonal insufficiency. Most cases involved adamantinomatous grade 1 type craniopharyngioma, with a mortality rate of 6%.Conclusion: Craniopharyngioma patients may remain asymptomatic until they acquire very large size and can presentwith features of raised intracranial pressure(ICP), visual disturbances and endocrinopathy. While there are multimodal treatment options, surgery stands as the cornerstone in managing this tumor.